Analysis of the Relationship between Modifiable Hypertension Risk Factors and Hypertension Incidence in the Adult Population - Sanggul, Andriyani Risma; Reviani, Nia; Rantung, Nolly O. H.; Puspitasari, Febtusia (Rifa'Institute, 2025)
Introduction: Hypertension, defined as systolic blood pressure >140 mmHg and diastolic >90 mmHg, is a major health issue that may lead to complications in various organs. It is influenced by modifiable and non-modifiable risk factors. Objective: This study aims to analyze the relationship between modifiable risk factors and the incidence of hypertension in Jemah Village, Sumedang Regency, in 2024. Method: This research used a quantitative cross-sectional design and was conducted in April 2024 in Jemah Village. The population included all residents aged ≥18 years, with 50 respondents selected using purposive sampling based on the Lemeshow formula. Central obesity was chosen as the primary variable due to its highest required sample size. Results and Discussion: Among the 50 respondents (24% male, 76% female), 70% were aged 18–64 years. Key modifiable risk factors identified included 66% non-smokers, 82% with excessive salt intake, 54% moderate physical activity, 44% with central obesity, and 54% with dyslipidemia. Chi-square analysis showed significant associations between hypertension and dyslipidemia (p=0.001), smoking (p=0.036), physical activity (p=0.046), and salt consumption (p=0.024). Conclusion: Hypertension was more prevalent among women. Dyslipidemia, smoking, physical inactivity, and high salt intake were significantly associated with hypertension.